Modeling Bounded Surfaces Using Cylindrical Coordinates Using GeoGebra AR - Espejo-Peña, Dennis Alberto (2023)
This research focuses on the modeling of bounded surfaces using parameterizations based on cylindrical coordinates, which is one of the topics of the multivariable calculus course, where it seeks to develop modeling and problem-solving skills in real context, being essential for this to develop geometric skills that allow sketching graphs in space. Therefore, the main objective of the research was to present a modeling case of a sludge decanting tank, through cylindrical coordinates, using the GeoGebra software in its Suite version for mobile devices, in addition to interacting with augmented reality (GeoGebra AR). With this, a didactic, dynamic, and iterative form is proposed where the inter-action between mathematics, engineering and technology is evidenced, and seeks to improve the teaching-learning experience.